Complex Valve Surgery in Elderly Patients: Increasingly Necessary and Surprisingly Feasible - Saha, Shekhar; Varghese, Sam; Ahmad, Ammar Al; Jebran, Ahmad Fawad; Waezi, Narges; Niehaus, Heidi; Baraki, Hassina; Kutschka, Ingo (The Thoracic and Cardiovascular Surgeon, 2020)
Objectives The increasing proportion of elderly patients in cardiac surgery poses additional challenges for the clinical management and leads to a higher operative risk due to multiple comorbidities of these patients. We reviewed the outcome of patients who were 75 years and older and underwent complex multiple valve surgery at our institution.Methods A retrospective review was performed to identify patients who were 75 years and older and underwent multiple valve surgery between January 2011 and May 2016 at our institution. Patients were assigned to one out of four subgroups: combined aortic and mitral valve surgery (group AM), aortic and tricuspid valve surgery (group AT), mitral and tricuspid valve surgery (group MT), and aortic, mitral, and tricuspid valve surgery (group AMT).Results A total of 311 patients underwent multiple valve surgery, of whom 119 (38.3%) were 75 years and older (median: 78 [25th–75th quartile: 76–80]). The estimated operative mortality (EuroSCORE II) in the overall cohort was 10.7%. The observed 30-day mortality was 4.2% (7% in group AM, 0% in group AT, 2.2% in group MT, 3.8% in group AMT; p = 0.685). Main complications were reexplorative surgery in 16%, adverse cerebrovascular events in 6.7%, prolonged mechanical ventilation in 10.1%, renal replacement therapy in 15.1%, nosocomial pneumonia in 15.1%, and pacemaker implantation in 18.5%.Conclusions This study demonstrates the feasibility of complex multiple valve surgery in elderly patients. The observed perioperative mortality was lower than predicted. However, we observed a substantial rate of adverse events; therefore, careful patient selection is required in this high-risk patient population.
Keywords: cardiac surgery; elderly; outcome; mortality; valve replacement